Antibody Peptide Based Antifungal Immunotherapy - Magliani, Walter; Conti, Stefania; Giovati, Laura; Zanello, Pier Paolo; Sperindè, Martina; Ciociola, Tecla; Polonelli, Luciano (Frontiers in Microbiology, 2012)
Fungal infections still represent relevant human illnesses worldwide and some are accompanied by unacceptably high mortality rates. The limited current availability of effective and safe antifungal agents makes the development of new drugs and approaches of antifungal vaccination/immunotherapy every day more needed. Among them, small antibody(Ab)-derived peptides are arousing great expectations as new potential antifungal agents. In this topic, the search path from the study of the yeast killer phenomenon to the production of Ab-derived peptides characterized by in vitro and in vivo fungicidal activity will be focused. In particular, Abs that mimic the antimicrobial activity of a killer toxin (“antibiobodies”) and antifungal peptides derived from antibiobodies (killer peptide) and other unrelated Abs [complementarity determining regions (CDR)-based and constant region (Fc)-based synthetic peptides] are described. Mycological implications in terms of reevaluation of the yeast killer phenomenon, roles of antibiobodies in antifungal immunity, of β-glucans as antifungal targets and vaccines, and of Abs as sources of an unlimited number of sequences potentially active as new immunotherapeutic tools against fungal agents and related mycoses, are discussed.